Factors that influence adherence to medication in adults with congenital heart disease (ACHD) - Halling, Tim; Akkermann, Steffen; Löffler, Friederike; Groh, Adrian; Heitland, Ivo; Haefeli, Walter E.; Bauersachs, Johann; Kahl, Kai G.; Westhoff-Bleck, Mechthild (Frontiers in psychiatry, 2021)
Objective: Innovative operative and interventional procedures have improved survival in congenital heart disease (CHD), and today more than 90% of these children reach adulthood. Consequently, adherence and psychosocial issues are becoming increasingly important because non-adherence to treatment recommendations worsens morbidity and mortality. This study aimed to identify factors modifying adherence to medication in adult congenital heart disease (ACHD).Methods: This cross-sectional study included 451 outpatients (female 47.9%, average age ± SD: 37.9 ± 12 years) from the ACHD department, who completed a questionnaire assessing medication non-adherence and individual barriers to treatment. Further assessments included psychological well-being (Hospital Anxiety and Depression scale; HADS), childhood traumatization, sociodemographic, and clinical data. Binary logistic regression analysis calculated the impact of these factors on drug adherence.Results: Of the 451 patients 162 participants (35.9%) reported to be non-adherent. In univariate analysis non-adherence to treatment was associated with smoking (P = < 0.001) and internet addiction (P = 0.005). Further factors negatively influencing adherence were the presence of depressive symptoms (P = 0.002), anxiety (P = 0.004), and childhood traumatization (p = 0.002). Factors positively associated with adherence were older age (P = 0.003) and more advanced heart disease as indicated by NYHA class (P = 0.01), elevated NT-proBNP (P = 0.02), device therapy (P = 0.002) and intermittent arrhythmias (P = 0.01). In multivariate analysis especially psychopathological factors such as depression (P = 0.009), anxiety (P = 0.032) and childhood traumatization (P = 0.006) predicted non-adherence.Conclusion: Adherence is a critical issue in the long-term management of ACHD. Identifying modifiable factors that worsen adherence offers the opportunity for targeted interventions. Depressive symptoms, anxiety, and adverse childhood experiences are amenable to psychosocial interventions, as well as cigarette smoking. Our study suggests that a multimodal and interdisciplinary treatment concept for the long-term management of adults with congenital heart disease could be beneficial. Whether it will further improve morbidity and mortality, should be assessed in prospective interventions.